Antiretroviral initiation of pregnant women and antenatal care booking practices in eThekwini District, KwaZulu-Natal, South Africa - Nomonde Nozulu; Bernard M. Gaede (AOSIS, 2018)
Background: The introduction of antiretroviral therapy (ART) in South Africa began as part of the prevention of mother-to-child transmission programme. For significant reduction of vertical transmission, early antenatal care booking and ART initiation are necessary. Aim: This study aimed to evaluate ART initiation and booking practices of women attending antenatal care in eThekwini district during financial years (FY) 2010/2011 and 2013/2014. Methods: An observational study used a retrospective chart review at four eThekwini district community health centres (CHC). From these CHCs, records of women that initiated ART in FY10/11 and FY13/14 were reviewed and compared for ART initiation delays and booking practices. Results: A total of 2749 pregnant women who attended antenatal care (ANC) at the study sites were found eligible for ART; of these, 49% (n = 1334) attended ANC in FY10/11 while 51% (n = 1414) attended in FY13/14. In FY10/11, 46% (n = 610) and 60 % (n = 855) of the women were initiated on ART during pregnancy. The mean gestational age at booking for FY10/11 was 20.88 (standard deviation [s.d.] = 5.6) and 18.40 (s.d. = 6.2) in FY13/14. The mean gestational age at ART initiation for women who initiated ART in FY10/11 was 26.30 (s.d. = 6.02) and in FY13/14 it was 19.06 (s.d. = 6.86). Conclusion: In FY13/14 ART initiations occurred within 4 days after booking. ANC booking before 20 weeks was found to have improved between the two years from 39% to 58%;however, on average, in both years women booked during the second trimester.